2011
DOI: 10.1021/ol200314v
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Regioselective Position-10 Bromination of Bacteriopyropheophorbide-a and Ring-B Reduced Pyropheophorbide-a

Abstract: Both bacteriopyropheophorbide-a and ring-B reduced pyropheophorbide-a on reacting with NBS (N-bromosuccinamide) undergo electrophilic bromination to provide 10-bromo analogs. The electronic nature of the substituents present at position-3 did not make any difference in regioselective outcome of the brominated products. These relatively stable brominated chlorins and bacteriochlorins provide an easy way of introducing a wide variety of functionalities, which could be extremely useful in developing improved agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Two different synthetic strategies were followed for the preparation of Chl–Bchl dyads with a diphenyl linkage (Scheme 1) or with an ester linkage (Scheme 2). For synthesis of the unsymmetrical dyads 7 and 8 , methyl 3‐acetyl bacteriopyropheophorbide 1 was obtained from Rhodobacter sphaeroides , [16] which on reacting with N ‐bromosuccinimide (NBS) gave the corresponding 10‐bromo analogue 3 in 66 % yield by following our previously reported methodology [17] . The chlorins 2 [methyl‐3‐(1′‐hexyloxy)ethyl‐3‐devinylpyropheophorbide‐a] [18] and 2 a [methyl‐3‐ethyl‐3‐devinylpyropheo phorbide‐a], differing only in the functional group at position‐3, were reacted individually with pyridinium tribromide to give the respective 20‐bromo analogues 4 and 5 , which were isolated in 87 % yield [17] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different synthetic strategies were followed for the preparation of Chl–Bchl dyads with a diphenyl linkage (Scheme 1) or with an ester linkage (Scheme 2). For synthesis of the unsymmetrical dyads 7 and 8 , methyl 3‐acetyl bacteriopyropheophorbide 1 was obtained from Rhodobacter sphaeroides , [16] which on reacting with N ‐bromosuccinimide (NBS) gave the corresponding 10‐bromo analogue 3 in 66 % yield by following our previously reported methodology [17] . The chlorins 2 [methyl‐3‐(1′‐hexyloxy)ethyl‐3‐devinylpyropheophorbide‐a] [18] and 2 a [methyl‐3‐ethyl‐3‐devinylpyropheo phorbide‐a], differing only in the functional group at position‐3, were reacted individually with pyridinium tribromide to give the respective 20‐bromo analogues 4 and 5 , which were isolated in 87 % yield [17] .…”
Section: Resultsmentioning
confidence: 99%
“…For synthesis of the unsymmetrical dyads 7 and 8 , methyl 3‐acetyl bacteriopyropheophorbide 1 was obtained from Rhodobacter sphaeroides , [16] which on reacting with N ‐bromosuccinimide (NBS) gave the corresponding 10‐bromo analogue 3 in 66 % yield by following our previously reported methodology [17] . The chlorins 2 [methyl‐3‐(1′‐hexyloxy)ethyl‐3‐devinylpyropheophorbide‐a] [18] and 2 a [methyl‐3‐ethyl‐3‐devinylpyropheo phorbide‐a], differing only in the functional group at position‐3, were reacted individually with pyridinium tribromide to give the respective 20‐bromo analogues 4 and 5 , which were isolated in 87 % yield [17] . Reaction of the 10‐bromobacteriochlorin 3 with the 20‐bromo chlorins 4 and 5 in presence 6 under Suzuki reaction conditions [19, 20] afforded the desired Chl–Bchl dyads 7 and 8 in 41 and 46 %, yield, respectively, along with the debrominated analogues 1 , 2 , and 2 a in 30–35 % yield (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…An in vivo biological investigation indicated that aside from the overall lipophilicity, the position of the substituents in the tetrapyrrolic skeleton also plays a crucial role in the long-term PDT response. [30] This report shows the utility of the Suzuki reaction [31] in synthesizing such candidates by introducing an additional functionality into the photosensitizer and their application in developing efficient agents for fluorescence imaging with and without PDT. [20][21][22] Photosensitizers with high tumor avidity are also being used as vehicles to deliver the desired imaging agents (radionuclides for nuclear imaging, fluorophores for optical-imaging agents, Gd III chelates for MR imaging) to the target site.…”
Section: Introductionmentioning
confidence: 90%
“…[29] For quite some time, our laboratory has also been interested in developing an efficient method for the regioselective synthesis of 20-meso-substituted purpurinimides, which could be utilized for developing a variety of photosensitizers (cationic, anionic, and targeted analogues) and bifunctional agents ( Figure 2). [30] This report shows the utility of the Suzuki reaction [31] in synthesizing such candidates by introducing an additional functionality into the photosensitizer and their application in developing efficient agents for fluorescence imaging with and without PDT. The regioselective introduction of a variety of substituents at the 20-meso-postion by the Suzuki reaction also provides an opportunity to alter the overall lipophilicity and target specificity of the molecule(s) by varying the nature of the substitution.…”
Section: Introductionmentioning
confidence: 90%
“…The intermediate tricarboxylic analog was reacted with gadolinium chloride (GdCl 3 ), and the conjugate 4 was isolated in 86 % yield. For introducing the Gd chelates at position‐20, HPPH methyl ester was first reacted with pyridinium bromide following our own methodology and afforded the corresponding 20‐bromo analog [23] . It was further reacted with 3‐( tert ‐butoxycarbonyl)phenylboronic acid pinacol ester under Suzuki reaction conditions and the intermediate 20‐benzoic acid derivative 2 was obtained in good yield after treating the intermediate with TFA.…”
Section: Resultsmentioning
confidence: 99%